Fixed Point Theorems for a Class of Weakly C-Contractive Mappings in a Setting of 2-Banach Space. (17th January 2013) - Saha, M.; Ganguly, Anamika
Abstract : In this paper, the authors have proved some existence theorems of fixed points for a class of weakly C-contractive mappings in a setting of 2-Banach space. The authors have supported the results with the help of suitable examples.